Burrow/Intensity Fluctuation of Field Rodents in Relation to the Development Stages of Vegetable Crops - Kumar, Parmesh; Pashan, S C; Sabhlok, V P; Singhal, R K (Annals of Arid Zone, 2016)
Fluctuations in burrow intensity of sympatric field murids in relation to the development stages of four sunUller vegetable crops, viz., bottle gourd, musk melon, sponge gourd and cucumber were recorded to be minimum at seedling stage (avemge, 5.50±<l.76 to 10.50±1.25 burrows per acre), which increased gmdually during vegetative growth and flowt.nng stagesand reached its peak (average, 32.75±1.31 to 52.50±2.20 burrows per acre) at the maturity stage. A linear trend in shifting of rodent abode from peripheral areas to inside title crop With the advancemcnt in crop maturity was noticed.